The influence of oxygen concentration on the rheological properties and flow of whole human blood - Valant, Andreja Zupančič; Ziberna, Lovro; Papaharilaou, Yannis; Anayiotos, Andreas; Georgiou, Georgios C. (My University, 2016)
Variations in blood oxygen concentrations are not only part of the normal physiology but they may also indicate various pathological conditions. In the present work, we examined the influence of oxygen concentration on the rheological properties of whole human blood. Blood samples were taken from two healthy donors, a male and a female, with hematocrits 0.47 and 0.42, respectively. In addition to the original samples of normal oxygen concentration (normoxemia), samples of different blood oxygen level were also prepared by using the perfusion cell equipped with a gas supply to induce either hypoxemia by driving out the oxygen saturating blood by nitrogen or hyperoxemia by saturating blood with oxygen. The rheology of the samples was measured using a Physica MCR 301 rheometer equipped with a sensor designed for hemorheology. The rheological results showed that oxygen-depleted blood exhibited lower viscosity and a lower yield stress when fitted to the Herschel-Bulkley constitutive model. Blood flow simulations of the effect of oxygen concentration on the local hemodynamics were also carried out in an idealized axisymmetric 75 % stenosis and in a realistic carotid bifurcation geometry constructed from MRI images obtained from a healthy male volunteer. The modified Herschel-Bulkley model with the Papanastasiou regularization was used to account for both the shear thinning and finite yield stress properties of blood. The results of this work showed that oxygen concentration affects the rheology and flow behavior of blood, suggesting compensatory responses under hypoxic conditions leading to a lower blood viscosity.
Keywords: Blood; Carotid bifurcation; Hemodynamics; Hemorheology; Herschel-Bulkley model; Oxygen concentration